The experience of nurses caring for children with intellectual disability - Alghamdi, Salmah; Alsaigh, Rasha; Alabdulaziz, Hawa; Dahlawi, Nada; Gmmash, Afnan (Frontiers in Psychiatry, 2025)
IntroductionChildren with disabilities are a vulnerable population and may have frequent hospital admissions. Therefore, nurses should be prepared to provide comprehensive care for this group of children. The aim of this research is to explore the experience of nurses caring for children with intellectual disabilities (ID).MethodsA qualitative descriptive design was used. A sample of eight registered nurses was recruited from different pediatric clinical settings through social media. The inclusion criteria were that nurses had to be registered, had experience providing care for children with ID for at least one year, and could speak English or Arabic. The data were collected using semi-structured interviews. Thematic analysis was used for data analysis.ResultsThe study revealed four major themes: (1) Communication barriers and the need for caregivers/parents’ interpretation, (2) Increased nursing demands due to complex care, (3) Adaptation to the greater complexity of care, and (4) Need for support for both nurses and caregivers/parents.ConclusionFindings from this study revealed that nurses are facing various challenges while committed to providing compassionate care for children with disabilities. Efforts should be made to provide support for families and nurses to ensure comprehensive care for children with ID.